Self-Assessment of Cultural Competence and Social Determinants of Health within a First-Year Required Pharmacy Course - Ulyana Kucherepa; Mary Beth O'Connell (MDPI AG, 2021)
As social determinants of health (SDOH) and health disparities are integrated with cultural competence in healthcare education, tools assessing multiple topics are needed. The Self-Assessment of Perceived Level of Cultural Competence (SAPLCC) survey is validated in student pharmacists and includes SDOH. The research objective was to determine if the SAPLCC survey can quantify cultural competence and SDOH course learning. First-year student pharmacists (N = 87) completed the SAPLCC survey anonymously before and after a social and administrative sciences course. The survey had 75 items with 1-4 Likert scales (4 high, total 300 points). All items were summed for the total score. Each item was assigned to a domain and factor. Factors were assigned to domains. The baseline total score was 190 ± 29 points, increasing by 63 ± 33 points post-course. All domains (i.e., knowledge, skills, attitudes, encounters, abilities, awareness), 13 of 14 factors, and total scores statistically increased. The SAPLCC tool captured student pharmacists' self-reported changes in cultural competence and SDOH.